FEATURES OF THE WORK ACTIVITY OF PRIMARY SCHOOL TEACHERS GENERAL EDUCATION SCHOOLS - Akhmadalieva N. O.; Nigmatullaeva D. J. (Academia Science Repository, 2023)
The working conditions of teachers at various levels of general education schools, according to the special assessment of working conditions (SAUT), are most often defined as acceptable. However, it does not include parameters for measuring intellectual, sensory, and emotional loads, as well as actual working conditions. At the same time, taking into account the criteria that the intensity of the labor process of teachers (intellectual, emotional sensory overload, etc.) corresponds to harmful working conditions, the interaction and mutual influence of these factors is reflected in the models of formation of occupational stress and further health disorders by the type of imbalance. The physiological feature of the teaching profession is a constant increased general metabolism, which is controlled by the thyroid gland, and its increased function leads to more.